Educação financeira: a visão de jovens universitários sobre as finanças familiares - Prado, André Brisola Brito (2015)
This article looks into how the families of young college students of a private university located in the major urban center of São Paulo relate to financial issues regarding consumption, credit, investments and decision-making. Having the financial question as a guide, we performed an analysis on whether these young college students and their families use the more rational bias or the more psychological one for decision-making, and, finally, whether there is any difference in financial behaviors among the different social class backgrounds in these families. The research quanti-qualitative methodology initially involved a bibliographical study followed by a field research, which utilized a questionnaire for data collection. The questionnaire was made available for the students of the business administration course, resulting in 226 valid answers. After data collection, a descriptive and interpretive analysis was performed based chiefly in Kahneman and Tversky's Prospect Theory, in Keynes's Liquidity Preference Theory - LPT - and Fisher's Loanable Funds Theory - LFT -, and also Prahalad's economic development in conjunction with Bauman's critical view. Results showed that it was not possible to determine which of the two aspects - the rational or the psychological - is the most used, but it was evidenced that both are used for decision making. It was possible to acknowledge that the college students and their families, regardless of their social class, have difficulty in financial planning in the short, medium and long terms. Finally, we observed that lack of knowledge and information about finances affect all social classes. Hence, this is a gap that needs to be filled. In this sense, the importance of the proposed Financial Education to be implemented in the various social contexts becomes evident. It will help create individuals able to make more assertive decisions and improve their personal finance management and become more integrated into society, where their choices will be more conscientious